Influence of Load on Friction Moment in Roller Screw - Fu Yongling; Gan Fajin; Qi Xiaoye; Wang Deyi (Jixie chuandong)
Firstly,the contact characteristic in the roller screw is introduced. Based on the Hertzian contact theory and the load distribution regulation of the roller screw,the model of friction moment is analyzed. The friction moment model shows that its influencing factors included in the half lengths of the major（ minor） of the contact ellipse and the sliding friction coefficient,on which the load of the roller screw has impact. The regularity between the load and the half lengths of the major（ minor） of the contact ellipse and the sliding friction coefficient values are discussed respectively. Finally,the relationship between the friction moment and the load of roller screw is obtained,which is compared to the results with the situation that regarding the sliding friction coefficient as constant. The result shows that,as the load increases 10% of rated load,the friction moment of roller screw increases correspondingly 16%. Furthermore,the consequence presents when the load larger than70% of rated load,the effects of the sliding friction coefficient changing with various load on the friction moment could not be neglected.